Long-term trends of poverty in Latin American countries - Altimir, Oscar (Estudios de Economía, 2016)
The article attempts an assessment of the long-term evolution of poverty in the four Latin American countries for which there is enough historical data. Argentina, Colombia, Chile,and Mexico represent a variety of the different national situations present in the region. Intertemporal comparability was preferred in order to depict the long-term trends of poverty and alternative estimates of poverty, corresponding to different degrees of deprivation, were used in order to assess the robustness of those trends. With the same purpose, the results of using poverty lines constant over time are compared with the trends obtained using poverty lines shifted as a result of medium-term growth. On the other hand, differences in income underestimation between surveys in each country were accounted for, in order to improve intertemporal comparison. Resulting country trends can be summarized as: poverty-reducing growth in the case of Colombia, an interrupted trend of poverty reduction in Mexico, the restoration of a broken trend of poverty reduction in Chile, and the emergence of poverty in the faltering economy of Argentina.